Muslim women's rights to mut'ah after dissolution of marriage under Islamic law: an absolute or limited right - Mohd, Azizah; Abd Malek, Normi (International Islamic University Malaysia, 2009)
A Muslim divorced woman in entitled to several rights after dissolution of her marriage. Those rights include maintenance during 'iddah, right to accommodation during 'iddah, right to the custody of children, right to any deferred mahr, right to a share in jointly acquired property and right to mut'ah or consolatory gift. These rights are meant to particularly to protect the interests and welfare of the divorced wife after dissolution of her marriage. Mut'ah is a property which is a replacement or an addition to the dower given to the divorced wife, to console and to assist her in facing life after divorce especially if she is divorced without just cause. This paper seeks to examine whether this right is absolute for all divorced wives or whether it is only limited to a particular situation where for example the wife is divorced without just cause or where the divorce is not initiated by the wife. For that purpose, the principle on mut'ah under the Shari'ah and provisions of Islamic law in Malaysia will be examined, to determine the extent of its application to the Muslim community in Malaysia.